Anti cancer composition - Abdul, Ahmad Bustamam; Arbab, Ismail Adam (2012)
The present invention relates to an anticancer composition use for cure or treatment of cancerous tumors, particularly human breast cancer and human prostate cancer. The pharmaceutical composition comprising an effective amount of dentatin, or dentatin derivative, and pharmaceutical acceptable carrier for the treatment of cancer. Preferably, the cancer is breast cancer of prostate cancer.